2022
DOI: 10.1155/2022/5896511
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Strength of Vitreous Ceramics Based on Lithium Disilicate and Lithium Silicate Reinforced with Zirconia for CAD/CAM

Abstract: The dental prosthesis market is rapidly evolving to meet patient and clinical demands. These new materials must have good flexural strength, toughness, aesthetic properties, and reliability in performance for structural applications. The present work aimed to compare the bending strength of 4 types of chairside lithium disilicate (Li2Si2O5) glass-ceramics used for dental prosthesis and to analyze the influence of heat treatment on the transformation of lithium metasilicate (Li2SiO3) into lithium disilicate. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…Colombo et al [ 59 ] reported that ZLS had the highest hardness when compared to hybrid ceramics and resin nano-ceramics. However, Corade et al [ 43 ] stated that LD showed a higher hardness than ZLS, which is inconsistent with the current findings. This might be related to the different methodology, ceramic specimen dimensions, absence of polishing procedures, and the use of non-crystallized ZLS, which differed from that used in the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Colombo et al [ 59 ] reported that ZLS had the highest hardness when compared to hybrid ceramics and resin nano-ceramics. However, Corade et al [ 43 ] stated that LD showed a higher hardness than ZLS, which is inconsistent with the current findings. This might be related to the different methodology, ceramic specimen dimensions, absence of polishing procedures, and the use of non-crystallized ZLS, which differed from that used in the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…The specimens were sectioned using a precision cutting machine (Isomet 5000, Buehler, Lake Bluff, IL, USA) with copious cooling water into the thicknesses of 0.5, 1, and 1.5 mm, with the same dimensions of the block, according to the International Organization of Standards (ISO standards 6872:2015) [ 43 ]. The specimens were polished using 500-grit silicon carbide discs for 60 s at a speed of 200 rpm with a water-cooling system, using a polishing machine (MetaServ 250 Grinder-Polisher with Vector Power Head, Buehler, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat treatment process improves and provides greater mechanical strength. It has been shown that the specimens with the lowest percentage of ZrO 2 exhibited greater crystallinity and corroborated the microstructural analysis (Corado et al, 2022). SEM analyses showed a greater amount of elongated crystals of lithium disilicate when comparing samples with higher percentage of ZrO 2 .…”
Section: Discussionsupporting
confidence: 70%
“…On the other hand, it has been shown that ZrO 2 being content of a lithium-disilicate ingot did not improve mechanical properties in studies comparing different pressed lithium disilicates (Hallmann et al, 2019;Sieper et al, 2017). Flexion tests showed that the addition of more than 10% of ZrO 2 reduced the flexural strength (Corado et al, 2022). The heat treatment process improves and provides greater mechanical strength.…”
Section: Discussionmentioning
confidence: 97%